Levels of Candidate Periodontal Pathogens in Subgingival Biofilm. (June 2016) - Oliveira, R.R.D.S.; Fermiano, D.; Feres, M.; Figueiredo, L.C.; Teles, F.R.F.; Soares, G.M.S.; Faveri, M.
In recent years, several new periodontal taxa have been associated with the etiology of periodontitis. A recent systematic review provides further support for the pathogenic role of 17 species/phylotypes. Thus, the aim of this study was to assess the prevalence and levels of these species in subjects with generalized chronic periodontitis (GChP; n = 30), generalized aggressive periodontitis (GAgP; n = 30), and periodontal health (PH; n = 30). All subjects underwent clinical and microbiological assessment. Nine subgingival plaque samples were collected from each subject and analyzed for their content of 20 bacterial species/phylotypes through the RNA-oligonucleotide quantification technique. Subjects from the GChP and GAgP groups presented the highest mean values for all clinical parameters in comparison with the PH group ( P < 0.05). Subjects with GChP and GAgP showed significantly higher mean levels of Bacteroidetes sp. human oral taxon (HOT) 274, Fretibacterium sp. HOT 360, and TM7 sp. HOT 356 phylotypes, as well as higher mean levels of Filifactor alocis, Fretibacterium fastidiosum, Porphyromonas gingivalis, Tannerella forsythia, and Selenomonas sputigena species than PH subjects ( P < 0.05). GAgP subjects presented higher mean levels of TM7 sp. HOT 356 and F. alocis than GChP subjects ( P < 0.05). A significantly higher mean prevalence of Bacteroidales sp. HOT 274, Desulfobulbus sp. HOT 041, Fretibacterium sp. HOT 360, and Fretibacterium sp. HOT 362 was found in subjects with GChP and GAgP than in PH subjects. Mean levels of P. gingivalis ( r = 0.68), T. forsythia ( r = 0.62), F. alocis ( r = 0.51, P = 0.001), and Fretibacterium sp. HOT 360 ( r = 0.41) were correlated with pocket depth ( P < 0.001). In conclusion, Bacteroidales sp. HOT 274, Desulfobulbus sp. HOT 041, Fretibacterium sp. HOT 360, Fretibacterium sp. HOT 362, and TM7 sp. HOT 356 phylotypes, in addition to F. alocis, F. fastidiosum, and S. sputigena, seem to be associated with periodontitis, and their role in periodontal pathogenesis should be further investigated.